Obstacles in weaning process: atypical presentation of Guillain-Barré Syndrome - Oh, Yin Lin; Ghazali, Abdul Majid; Bahruddin, N.A. (2023)
Guillain-Barré syndrome (GBS) is an immune-mediated acute polyneuropathy with an annual incidence of 0.81-1.89 cases per 100,000 persons worldwide. It is classically diagnosed based on its distinctive clinical features, which consist of an acute onset ascending sensorimotor neuropathy following a prodromal upper respiratory tract or gastrointestinal tract infection4. These infections are thought to trigger the immune response that causes GBS. An atypical presentation poses a diagnostic challenge for healthcare professionals due to the heterogenous presentation and diverse diagnostic possibilities.